(3cJGH GdJQab aj GdYWQs - (3jYbhH Hf ESMGb GdeSjMji Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg cKjQkG gPG cJGH GdJQab ai GdYWQ CHhGH UfYI GdeSc s
(3BNQgG (B:s
(3Ke jMTi hjbdi Ke jdbi ai GdScQ hjYbO GdeTHc hjdbi Ydjg aGYQa Pdc s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs